1992
DOI: 10.1126/science.258.5084.981
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Long-Term Trends of Oxygen-18 Isotope Composition of Precipitation and Climate

Abstract: Stable isotope ratios of oxygen ((18)O/(16)O) and hydrogen (D/H) in water have long been considered powerful indicators of paleoclimate. However, quantitative interpretation of isotope variations in terms of climate changes is hampered by a limited understanding of physical processes controlling the global isotope behavior. Analysis was conducted of time series of (18)O content (delta (18)O) of monthly precipitation and surface air temperature available through the International Atomic Energy Agency-World Mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
419
5
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 709 publications
(459 citation statements)
references
References 23 publications
26
419
5
9
Order By: Relevance
“…Previous work in Indonesia (e.g. Griffiths et al, 2009;Lewis et al, 2010) has demonstrated that the dominant process controlling the d 18 O of monsoon rainfall, and hence the speleothem calcite, is the 'amount effect' (Rozanski et al, 1992). This process, whereby lower (higher) d 18 O values correspond with higher (lower) rainfall, is underpinned by the strong co-variation with Mg/ Ca (Fig.…”
Section: Host Rock Contribution To Dcfmentioning
confidence: 99%
“…Previous work in Indonesia (e.g. Griffiths et al, 2009;Lewis et al, 2010) has demonstrated that the dominant process controlling the d 18 O of monsoon rainfall, and hence the speleothem calcite, is the 'amount effect' (Rozanski et al, 1992). This process, whereby lower (higher) d 18 O values correspond with higher (lower) rainfall, is underpinned by the strong co-variation with Mg/ Ca (Fig.…”
Section: Host Rock Contribution To Dcfmentioning
confidence: 99%
“…While the spatiotemporal relationships between the NAO and meteorological variables (e.g., precipitation amount and air temperature) are well-constrained [e.g., Castro-Díez et al, 2002;Hurrell, 1995;Munoz-Diaz and Rodrigo, 2003;Thompson and Wallace, 2001;Trigo et al, 2002;Uvo, 2003;Zveryaev, 2004] [Bowen and Revenaugh, 2003;Bowen and Wilkinson, 2002;Jouzel et al, 2000;Rozanski et al, 1992], whereas our primary focus is the d 18 O p -NAO relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes in precipitation have already been investigated for a few decades and have been found to strongly reflect climatic conditions, especially temperature [Dansgaard, 1964;Rozanski et [Eicher, 1995], and in tree rings [Saurer et For internal and interlaboratory calibrations we used three different cellulose standards: "Merck," "IAEA-C3," and "WSL." Merck is a commercial cellulose available as powder, mostly used for thin-layer chromatography.…”
Section: Introductionmentioning
confidence: 99%